Advances in therapeutic agents targeting quiescent cancer cells - Wan Najbah Nik Nabil; Zhichao Xi; Mengfan Liu; Yang Li; Mu Yao; Tao Liu; Qihan Dong; Hongxi Xu (Compuscript Ltd, 2022)
Quiescent cancer cells (QCCs) reversibly reside in G0 phase, thus allowing them to survive chemotherapy and radiotherapy, which generally target proliferating cells. Surviving QCCs may re-proliferate, and consequently result in cancer progression, recurrence, and metastasis. Therefore, understanding the key players governing QCC survival and activation is crucial for developing QCC-targeting agents. This review presents an overview of (1) the mechanisms underlying the regulation of QCC status and (2) recent advances in the development of QCC-targeting therapeutic agents and their underlying mechanisms. The development of effective therapeutic modalities that target QCCs may enable new cancer treatments to prevent cancer progression and recurrence.